The Role of a Mother in Education of Children According To The Perspective of The Quran - Ranam, Sanudin; Priyono; Muslim, Ibnu Fihan; Apipudin (CV ODIS, 2024)
The mother's role as an educator is very important, including the duties of breastfeeding and protecting and educating children. Psychological research shows that the mother's presence from the beginning of a child's growth is crucial because early childhood is a critical period for the child's physical, intellectual, personality, and spiritual formation. Based on the Al-Qur'an in Surah Al-Baqarah Verse 233, Luqman Verse 14, and Al-Ahqaf Verse 15, there is important education that must be instilled in children, including the education of aqidah and Luqman's advice to his children. This research is library research with data collection methods in the form of documentation and interpretation of the Al-Qur'an. The aim is to understand the role of mothers in educating children according to Surah Al-Baqarah Verse 233, Luqman Verse 14, and Al-Ahqaf Verse 15. The results show the importance of children's education from the womb, as well as the mother's role in breastfeeding, protecting, educating, and forming aqidah, responsibility, and gratitude in children. Breastfeeding with breast milk supports the child's health and begins the educational process from the breastfeeding period.